FACTORS AFFECTING CAPITAL STRUCTURE IN FOOD AND COMPANIES BEVERAGES LISTED ON THE EXCHANGE INDONESIAN SECURITIES (IDX) - Putri Handayani Bachtiar; Muchriana Muchran; Muhammad Khaedar Sahib (International Journal of Economic Research and Financial Accounting, 2024)
The aim of this research is to determine the factors that influence the capital structure of food and beverage companies listed on the Indonesia Stock Exchange (BEI). The population in this study is listed food and beverage companies listed on the Indonesia Stock Exchange (BEI), with a sample of 24 companies. This research was conducted using quantitative methods with the variables used in this research being Profitability, Liquidity, Company Size and Company Growth. The data analysis techniques used in this research are the classical assumption test, multiple linear regression analysis, hypothesis testing with partial tests (t tests), simultaneous F tests, and determination tests with the help of SPSS software. The results of this research show that Profitability has a negative and significant effect on the capital structure of food and beverage companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 period. Liquidity has a negative and significant effect on the capital structure of food and beverage companies listed on the Stock Exchange Indonesia (BEI) for the 2020-2022 period, Company size has a negative and significant effect on the capital structure of food and beverage companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 period, Company Growth has no effect on the capital structure of food and beverage companies listed listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 period